UTILIZATION OF DOCUMENTARY FILMS AS INFORMATION MEDIA FOR PROFILES AND EXPERTISE COMPETENCIES - Fajar Muharam; Tuty Mutiah; Raja Syamsidar (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the utilization of documentary films as an information medium in presenting the profile and professional competencies of an educational institution. Documentary films, as audio-visual media, possess the strength to deliver factual, persuasive, and educational information by integrating visual elements, narration, sound, and authentic testimonials. This research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The research subjects involve institutional representatives and audiences who viewed the documentary film. The findings indicate that documentary films are effective in enhancing audience understanding of the institution’s profile and areas of expertise. The structured and fact-based presentation of information helps build credibility and strengthen the institution’s positive public image. Furthermore, the engaging audio-visual elements increase audience interest and involvement in receiving the conveyed messages. This study concludes that documentary films can serve as a strategic and relevant information medium in institutional communication, particularly in efforts to build image, enhance reputation, and broaden public outreach.